(untitled) (Research, Society and Development, 2023)
The present research aims to examine the literature on the impact of the Covid-19 pandemic on the mental health of nursing professionals. An integrative literature review was conducted, analyzing studies published between 2019 and 2021, using the databases National Library of Medicine, Nursing Database, and Scientific Electronic Library Online. It was possible to identify that the Covid-19 pandemic had a direct impact on the mental health of nursing workers. The literature highlights the main problems caused by the pandemic context, including depression, anxiety, feelings of distress, sadness, and guilt, changes in appetite and sleep, as well as elevated levels of stress and irritability. In this context, public health policy actions aimed at protecting nursing workers during the pandemic and post-Covid-19 have become essential for maintaining the psychological well-being of these professionals. However, it is considered essential to conduct further studies that investigate the implemented actions aimed at protecting the workers, as well as ensuring working conditions and physical infrastructure for the continued provision of social protection at different levels of care even after the pandemic.